2018
DOI: 10.1080/17518253.2018.1458160
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasound-promoted green synthesis of 1,4-dihydropyridines using fuctionalized MWCNTs as a highly efficient heterogeneous catalyst

Abstract: View related articles View Crossmark data Citing articles: 1 View citing articles Ultrasound-promoted green synthesis of 1,4-dihydropyridines using fuctionalized MWCNTs as a highly efficient heterogeneous catalyst

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 42 publications
(23 citation statements)
references
References 73 publications
0
23
0
Order By: Relevance
“…Clean and green reaction conditions, shorter reaction times, high product yield, heterogeneity, and catalyst reusability are some of the main advantages of the reported method. 44 Further, graphene oxide-supported PdRuNi@GO nanomaterial was synthesized and characterized by TEM, HRTEM, XRD, and XPS techniques. The TEM image of the synthesized PdRuNi@GO showed that the particles are distributed on the support of graphene oxide, as shown in Fig.…”
Section: Non-magnetic Metal Oxide/mixedmetal Oxide Nanoparticles Catamentioning
confidence: 99%
“…Clean and green reaction conditions, shorter reaction times, high product yield, heterogeneity, and catalyst reusability are some of the main advantages of the reported method. 44 Further, graphene oxide-supported PdRuNi@GO nanomaterial was synthesized and characterized by TEM, HRTEM, XRD, and XPS techniques. The TEM image of the synthesized PdRuNi@GO showed that the particles are distributed on the support of graphene oxide, as shown in Fig.…”
Section: Non-magnetic Metal Oxide/mixedmetal Oxide Nanoparticles Catamentioning
confidence: 99%
“…The diffusion of the Hantzsch reaction in building up the 1,4-DHPs libraries is mainly to be attributed to the discovery that ammonia could be efficiently replaced by ammonium acetate. [30,31] Furthermore, the use of several different homogeneous and heterogeneous catalysts, [32] as well as ionic liquids, [33] organocatalysts [34,35] and alternative energy sources, [35][36][37][38][39] can accelerate the reaction times and increase the reaction yields. Several past reviews provide a complete survey on the synthetic methodologies for realizing the Hantzsch reaction, as well as on the libraries of the resulting structurally different 1,4-DHPs.…”
Section: The Hanztsch Reactionmentioning
confidence: 99%
“…The temperature of these bubbles is around 5000 K, with pressures of roughly 1000 atm . Thus, the ultrasonic irradiation provided a green, powerful, rapid, safe, clean and efficient condition for synthetic chemistry …”
Section: Introductionmentioning
confidence: 99%